Izolacija negibnih točk preslikav na kompaktnem poliedru - Borštnik, Andrej (Matrika, 2014)
This article considers the isolation of fixed points of maps on compact polyhedra. First we have a look at what polyhedra are and then we show a few properties we are going to need later. We also define simplicial maps which we need for deforming the map. We show that every map can be slightly modified into a simplicial map which has isolated fixed points. That proves it is possible to isolate fixed points of an arbitrary map on a compact polyhedron. The property that all maps can be slightly modified to a map with isolated fixed points is a topological invariant and therefore transfers to all spaces homeomorphic to polyhedra.
Keywords: kompaktni poliedri; negibne točke; simplicialne preslikave